2015
DOI: 10.1177/0040517514561924
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and analysis of airflow in the condensing zone of compact-siro spinning

Abstract: Compact-siro spinning is a new kind of spinning technique that combines compact spinning and siro spinning, and is widely put into practice. In this paper, a simulation and characterization of the flow field in the condensing zone are made by computational fluid dynamics software. It mainly includes the distribution rules of static pressure and velocity. According to the relative references and factory condition, several orthogonal and control experiments have been done. Through testing the strength, evenness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 3 publications
0
12
0
2
Order By: Relevance
“…The ranges of the axes are set as follows: X-axis [0, 19]; Y-axis [-6, 12], and Z-axis [0, 3] in REGION [12]. As shown in Figure 3(b), the faces 1, 2, 3, 4, and 5 are specified as the pressure entrance faces, the face in the negative pressure area of the shaped tube is specified as the pressure exit face, and the others are specified as the wall [13]. The pressure entrance is at an atmosphere condition, and the exit is in a negative pressure (P=2.35 kPa).…”
Section: Solving Parameter Settingmentioning
confidence: 99%
“…The ranges of the axes are set as follows: X-axis [0, 19]; Y-axis [-6, 12], and Z-axis [0, 3] in REGION [12]. As shown in Figure 3(b), the faces 1, 2, 3, 4, and 5 are specified as the pressure entrance faces, the face in the negative pressure area of the shaped tube is specified as the pressure exit face, and the others are specified as the wall [13]. The pressure entrance is at an atmosphere condition, and the exit is in a negative pressure (P=2.35 kPa).…”
Section: Solving Parameter Settingmentioning
confidence: 99%
“…Çıkış silindirleri sonuna eklenen farklı yüzeydeki yapılar a) geleneksel eğirme sistemi b) düz yüzeyde kuru eğirme c) düz yüzeyde ıslak eğirme d) kuru yüzeyde ıslak eğirme e) yivli yüzeyde ıslak eğirme [40] Şekil 10. Kompakt-siro çekim bölgesine ilave edilen hava kanallı yapı [41].…”
Section: Eği̇rme Teknoloji̇leri̇nde Yapilan Geli̇şti̇rmelerunclassified
“…Their works concluded that the flow field distribution largely depends on the roller lattice-apron type and subsequently affects the yarn properties in the condensing zone. Han et al 25,26 studied the condensing effects of different suction slots, where parallel-shaped slots, oblique parallel-shaped slots, and V-shaped slots were studied. The fiber trajectory and flow field in the condensing zone were simulated and characterized in a compact Siro spinning machine with a lattice apron.…”
mentioning
confidence: 99%